2007
DOI: 10.1503/cmaj.060963
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia: its etiology, effects and treatment

Abstract: CMAJ 2007;176(8):1113-20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
409
1
34

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(452 citation statements)
references
References 61 publications
8
409
1
34
Order By: Relevance
“…Monogenic disorders that cause abnormal levels of plasma cholesterol and triglycerides have received much attention due to their role in metabolic dysfunction and cardiovascular disease. While these disorders often present clinically during adulthood, some present in the pediatric population and can have serious consequences if misdiagnosed or untreated [4]. Hypertriglyceridemia is defined as having plasma triglyceride above the 95th percentile for age and sex [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monogenic disorders that cause abnormal levels of plasma cholesterol and triglycerides have received much attention due to their role in metabolic dysfunction and cardiovascular disease. While these disorders often present clinically during adulthood, some present in the pediatric population and can have serious consequences if misdiagnosed or untreated [4]. Hypertriglyceridemia is defined as having plasma triglyceride above the 95th percentile for age and sex [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence suggests that presentation during infancy can be heterogeneous and may include other signs such as pallor, anemia, jaundice, irritability, and diarrhea. These manifestations are variable in the time and severity of presentation [4]. One study conducted in Quebec, Canada, in which LPL deficiency was demonstrated in 16 infants who presented with heterogeneous features, irritability, pallor, anemia, and gastrointestinal bleed, while others presented with splenomegaly and positive family history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-pharmacologic treatment of hypertriglyceridemia includes weight reduction, dietary modification and physical activity. Among dietary modifications, reducing intakes of overall energy and dietary fat, including saturated and trans fat intake, but increasing o-3 fatty acids, are often recommended (Yuan et al, 2007). A wise choice of both the amount and the type of dietary fat is helpful for the management of hypertriglyceridemia.…”
Section: Introductionmentioning
confidence: 99%
“…Isso porque, segundo alguns pesquisadores, programas com mais de 12 semanas de duração são capazes de promover a redução do LDL-colesterol e do TRI, e aumento do HDL-colesterol 36,37,38 , o que foi confirmado por Lavis et al 2 na população de lesão medular.…”
Section: Escala De Borgunclassified